Resilience, plasticity and dynamics of Aleppo pine forests - Borghetti M; Moretti N (Forest@, 2023)
Post-fire natural regeneration of Aleppo pine forest in the Gargano promontory (Southern Italy) is documented by means of photographs taken soon after fire and some years later. The potential of pine for adaptation to climate change and fire disturbance through its phenotypic plasticity is highlighted, and future dynamics of Aleppo pine forests and management perspectives are considered.